2017
DOI: 10.1111/cmi.12814
|View full text |Cite
|
Sign up to set email alerts
|

The bile salt sodium taurocholate inducesCampylobacter jejuniouter membrane vesicle production and increases OMV-associated proteolytic activity

Abstract: Campylobacter jejuni, the leading cause of bacterial acute gastroenteritis worldwide, secretes an arsenal of virulence-associated proteins within outer membrane vesicles (OMVs). C. jejuni OMVs contain three serine proteases (HtrA, Cj0511, and Cj1365c) that cleave the intestinal epithelial cell (IEC) tight and adherens junction proteins occludin and E-cadherin, promoting enhanced C. jejuni adhesion to and invasion of IECs. C. jejuni OMVs also induce IECs innate immune responses. The bile salt sodium taurocholat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 104 publications
4
33
2
Order By: Relevance
“…Our data are to some extent different from those recently reported by Elmi and co-workers 45 studying the effects of taurocholate on C . jejuni OMVs.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our data are to some extent different from those recently reported by Elmi and co-workers 45 studying the effects of taurocholate on C . jejuni OMVs.…”
Section: Discussioncontrasting
confidence: 99%
“…Bile did however not affect CDT abundance in the bacteria. None of the Campylobacter invasion antigens (Cia) were detected in OMVs in our setting, and neither was CiaB detected in OMVs after growth in taurocholate 45 . This is in line with that the flagellum is known to be the secretion apparatus for Cia proteins 20 and CiaB protein was detected in bacteria only but with no alteration in the protein level by low bile at 20 h. Increased transcription and translation of ciaB gene in bacteria was previously shown with high concentration of bile 46 , 47 .…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…According to Taheri et al [176] composition of the C. jejuni MVs depends on growth temperature and it has implications for the outcome of colonization and pathogenicity of this bacterium in different hosts. Elmi et al [185] indirectly confirmed the abovementioned findings by Taheri et al [184] using bile salt sodium taurocholate. After treatment with this bile salt, C. jejuni outer MV production increased, with increased MVs-associated proteolytic activity as a consequence.…”
Section: Gram Negative Bacteriasupporting
confidence: 56%
“…A more detailed experimental analysis revealed that the Cj0511 serine peptidase, which was shown to be present in C. jejuni OMVs in conjunction with the HtrA and Cj1365c proteases [ 94 ], is essential for chicken colonization. The findings that OMVs produced in the presence of the bile salt taurocholic acid exerted elevated proteolytic activity and were found to be required for C. jejuni invasion and transmigration in vitro underlined the functions of the secreted proteases in C. jejuni virulence and intestinal pathogenesis [ 120 ]. Taken together, all these findings provided the first evidence that the other proteases of C. jejuni might represent excellent targets for antibacterial therapy and the protection of lifestock from C. jejuni colonization.…”
Section: Other Proteases Identified In C Jejunimentioning
confidence: 99%